Intervensi Social Skills Training Pada Pasien Skizofrenia: Reviu Literatur - Sriyk H, Sriyk H; Mustikasari, Mustikasari (Poltekkes Kemenkes Kendari, 2023)
Deficiencies in thinking, perception, unnatural or dull affect and social behavior, including decreased or inability to communicate as well as experiencing difficulty in carrying out activities experienced by schizophrenia sufferers, indicate that they need training in communication and social skills. This requires social skills training intervention in order to improve communication abilities and social skills. This article was written to determine social skills training interventions for schizophrenia patients through a literature study search, the writing method was carried out using a journal review approach from Pro Quest, Oxford, Sage Journal, Scopus, science Direct and PubMed with the keywords Social Skills Training AND Schizophrenia in each journal. The search was carried out from June 2023-August 2023 with the inclusion criteria being clinical trial articles, year of publication in the last 10 years, namely 2023 to 2023, English language, and quantitative methods. The results of this study stated that the initial search yielded 8,332 publications, which ultimately resulted in 9 studies reviewed, in the form of quantitative research, for interventions defined as SST need to include core behavioral techniques such as instruction in skills, live or recorded modeling or role-play exercises, and positive and corrective feedback. Studies should include samples with a diagnosis of schizophrenia. The studies reviewed show that Social skills training interventions can improve social skills or social adaptive functioning, increase adaptive behavior and improve negative symptoms in schizophrenia patients.